Synchronous malignancy of stomach and kidney: an unusual combination: a case report - Chaturvedi, Shruti; Subbarayan, Boopathi; Subbaraj, Saravanakumar; Tirougnanassambandamourty, Tirou Aroul; Smile, Samuel Robinson (International Surgery Journal, 2020)
Synchronous occurrence of primary gastric cancer with primary renal cell carcinoma (RCC) is exceedingly rare. We report a case of a 70 years old gentleman who presented with a history of epigastric fullness and tarry stools from 1 month, along with significant weight loss which he was unable to quantify. Esophagogastroduodenoscopy showed ulceroproliferative growth in the antropyloric region of stomach causing complete outlet obstruction. Histopathology revealed poorly differentiated mucinous adenocarcinoma. Contrast enhanced computed tomography (CECT) abdomen showed an asymmetrical circumferential growth in the antropyloric region leading to obstruction. A heterogeneously enhancing hypervascular mass was also visualized over the lower pole of left kidney with an initial impression of metastasis. A concomitant radical subtotal gastrectomy and radical left nephrectomy was performed. Pathological examination confirmed gastric adenocarcinoma (T4a) and renal cell carcinoma-RCC (T3a). Most of the operable synchronously occurring second primary malignancy (SPM) can be resected in a single stage.